Tax Knowledge and Understanding in Individual Taxpayer Compliance: Literature Review and Case Study of the Kebon Jeruk Satu Tax Office - Izzat, Fadjar Hibbatul; Sahara, Ana Farida; Putra, Yananto Mihadi (Baca Dulu Publisher, 2025)
This study aims to analyze the influence of tax knowledge and understanding on individual taxpayer compliance through a literature review and a case study at the Primary Tax Office (KPP) Jakarta Kebon Jeruk Satu. The literature review indicates that the majority of previous research concludes that tax knowledge and understanding have a positive impact on taxpayer compliance. The case study reveals that individual taxpayers with more than one employer often experience tax underpayment due to the repeated application of Non-Taxable Income (PTKP) by each employer. This phenomenon leads many taxpayers to feel that they are not responsible for the resulting tax shortfall and therefore choose not to submit their annual tax return. These findings suggest that low compliance levels are driven by a lack of understanding and awareness of the self-assessment system and prevailing tax regulations. Therefore, enhancing tax education and outreach to improve knowledge and understanding among taxpayers and employers is crucial to increase compliance and national tax revenue.